Multi-dimensional imaging - Javidi, Bahram; Tajahuerce, Enrique; Andres, Pedro (John Wiley & Sons Inc., 2014)
Multi-dimensional Imaging brings together research from various fields, including physics, optics, signal processing and image capture and display techniques to describe fundamentals as well as advanced multi-dimensional imaging and visualization. With contributions from leading researchers from across these fields, this book is a comprehensive reference for the imaging technology research community. It describes recent developments as well as the prospects and challenges in modern multi-dimensional imaging sciences and engineering; covering the most recent technologies such as high speed digital holography, compressive sensing, computational imaging, real-time 3D integral imaging, 3D TV, polarimetric imaging, biomedical applications, and advanced imagers. -- Key features:. Combines introductory material with new advances in multi-dimensional imaging and applications. Covers the integration of physics, optics, algorithms, and computational imaging providing a broad overview of advanced multi-dimensional imaging systems. Discusses a range of applications including 3D, biomedical applications, entertainment, education, security and defence.